2010
DOI: 10.1073/pnas.0914448107
|View full text |Cite
|
Sign up to set email alerts
|

Transmission distortion by loss of p21 or p27 cyclin-dependent kinase inhibitors following competitive spermatogonial transplantation

Abstract: Spermatogonial stem cells (SSCs) undergo self-renewal division to support spermatogenesis. Although several positive regulators of SSC self-renewal have been identified, little is known about the mechanisms that negatively regulate SSCs. Here we developed a novel transplantation assay for SSCs and demonstrate that p21 and p27 cyclin-dependent kinase inhibitors play critical roles in SSC self-renewal and differentiation. Overexpression of p21 or p27 abrogated proliferation of cultured SSCs in vitro, and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Previous studies show that p27 Ϫ/Ϫ mice have increased Sertoli cell number and daily sperm production, resulting in larger testes compared with wild-type mice (41,43). Similar results were observed in Ppard Ϫ/Ϫ mice in the present study compared with p27 Ϫ/Ϫ mice because lower expression of p27 was associated with increased Sertoli cell number, enhanced sperm production, and larger testes.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies show that p27 Ϫ/Ϫ mice have increased Sertoli cell number and daily sperm production, resulting in larger testes compared with wild-type mice (41,43). Similar results were observed in Ppard Ϫ/Ϫ mice in the present study compared with p27 Ϫ/Ϫ mice because lower expression of p27 was associated with increased Sertoli cell number, enhanced sperm production, and larger testes.…”
Section: Discussionsupporting
confidence: 80%
“…Mice deficient in S-phase kinase-associated protein 2 (Skp2), which mediates ubiquitin-dependent degradation of p27, exhibit a progressive loss in spermatogenic cells (36). Conversely, testes from p27-knockout mice are significantly larger (37) and contain increased numbers of type A spermatogonia (38), and EpCAM + spermatogonia from the knockout mice proliferate more actively than those from wild-type mice do (39). We found that Cirp decreases the protein level of p27 and increases cell proliferation via Dyrk1b in MEFs and the spermatogonial cell line and that the p27 protein level and cells in G0 phase were increased in Cirp-deficient undifferentiated spermatogonia.…”
Section: Discussion Numbers and Proliferative Activity Of Undifferentmentioning
confidence: 58%
“…FGF2 is expressed by Sertoli cells and was reported to enhance the ability of GDNF to maintain SSC proliferation in vitro (26,32,36,37). However, no significant differences were detected by ELISA in FGF2 protein levels in testes of 8-wk-old WT, Het, and cKO mice (Fig.…”
Section: Effects Of Cko On Genes Involved In Spermatogonial Developmentmentioning
confidence: 83%